Metabolic Engineering of Sesquiterpene Metabolism in Yeast - Takahashi, Shunji (2007)
Terpenes are structurally diverse compounds that are of interest because of their biological activities and industrial value. These compounds consist of chirally rich hydrocarbon backbones derived from terpene synthases, which are subsequently decorated with hydroxyl substituents catalyzed by terpene hydroxylases. Availability of these compounds is, however, limited by intractable synthetic means and because they are produced in low amounts and as complex mixtures by natural sources. We engineered yeast for sesquiterpene accumulation by introducing genetic modifications that enable the yeast to accumulate high levels of the key intermediate farnesyl diphosphate (FPP). Co-expression of terpene synthase genes diverted the enlarged FPP pool to greater than 80 mg/L of sesquiterpene. Efficient coupling of terpene production with hydroxylation was also demonstrated by coordinate expression of terpene hydroxylase activity, yielding 50 mg/L each of hydrocarbon and hydroxylated products. These yeast now provide a convenient format for investigating catalytic coupling between terpene synthases and hydroxylases, as well as a platform for the industrial production of high value, single-entity and stereochemically unique terpenes.